Objectively measuring subjectively described traits: geographic variation in body shape and caudal coloration pattern within Vieja melanura (Teleostei: Cichlidae) - McMahan, Caleb D. (2017)
Vieja melanura is a Neotropical cichlid occurring in the Petén-lake district systems of Guatemala, as well as the Río Grijalva-Usumacinta basin, and other systems in Southern México, Belize, and Guatemala. A caudal stripe, extending forward from the caudal peduncle, is characteristic of this species. This stripe is sloped downward in nearly all individuals of V. melanura, but the degree of the slope is highly variable throughout its range. The slope and shape of the stripe has previously been used in diagnosing and differentiating between species of Vieja. The purpose of this study was to use objective methods to investigate morphological variation in the caudal stripe and body shape throughout the range of V. melanura. We studied geometric morphometric analyses of body shape and empirical measurements of the slope of the caudal stripe in 215 specimens of V. melanura. We also used the mitochondrial cytochrome b marker to study population level patterns within V. melanura. Results from our analyses showed significant geographic variation in body shape and patterns of coloration with little mitochondrial phylogeographic structure. These patterns likely correspond to differences in riverine habitats throughout the species’ distribution. In conclusion, these results can be used to inform other studies of color and shape variation as it applies to taxonomy and systematics.